Halal small and medium enterprises (SMEs) in direct selling industry: scenario in Malaysia - Abdullah, Moha Asri (HH Publisher, 2018)
Halal industry has become a new growth sector in the global economy and direct selling industry has expanded its value tremendously over decades. In view of fast rising halal industry and direct selling industry, there has been an increase in Halal Small and Medium Enterprises (SMEs) involves, not only as distributor enterprises but also the stockists and Halal manufacturers. Malaysia is not exceptional to this when there has been a commendable growing contribution of the industries to the gross domestic product (GDP). This growth has not excluded halal SMEs in direct selling industry. Nonetheless, Halal SMEs in the direct selling industry has not been explored that much. Their types of products, ownership status, location, capital utilisation, their competition, employee, their issues and prospects are not much being researched. This paper attempts to fill up this vacuum by researching Halal SMEs in direct selling industry based on a survey conducted on 61 Halal SMEs in Malaysia. The findings reveal that a substantial proportion of them market products like vitamin, supplementary food and other health food supplements. A significant proportion of them used their own capital to run their businesses and more than two-third has reached the status of Good Manufacturing Practices (GMP). Halal SMEs are also confronted by many issues such as competition, limited sources of capital, debt from clients and accessibility to assistance provided by the authorities. The paper concludes that a more vibrant Halal SMEs in direct selling could be realised, should a more proactive policy supports could be made available.